2017
DOI: 10.1016/j.tjog.2017.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Learning curve in concurrent application of laparoscopic and robotic-assisted hysterectomy with lymphadenectomy in endometrial cancer

Abstract: Operative time was longer but Lymph node dissection was easier in RSS. Learning curve for LSS to maintain similar surgical quality as RSS was not observed. The concurrent use of robotic platform in the initial practice of minimally invasive staging surgery could optimize surgical technique for LSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 34 publications
1
17
1
Order By: Relevance
“…Our study did not confirm previous reports [17,21,23,24] concerning higher operative time when robotic assistance was used. In this study, similar operative times were observed in all groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study did not confirm previous reports [17,21,23,24] concerning higher operative time when robotic assistance was used. In this study, similar operative times were observed in all groups.…”
Section: Discussioncontrasting
confidence: 99%
“…In a study, in the learning curve of laparoscopic hysterectomy, the first 10 procedures were done in a mean time of 180 minutes and decreased to 75 minutes in the 90-100th patients. 21 In the medical center of the present study, the nursing staff, equipment, and engineering were also in training period (learning curve), and the effect of these factors was also evident in the operative time. For instance, unchecked instruments, camera, and monitoring system exhibited problems during operation which took time to solve each of them.…”
Section: Operation Timementioning
confidence: 66%
“…Minimally invasive surgery using laparoscopy is the preferred approach, when feasible, for the management of painful DIE [ 4 ]. Robotic laparoscopy (RL) has proven its feasibility in DIE, permitting better dexterity and having a shorter learning curve in comparison with conventional laparoscopy [ 11 , 12 ]. There are no differences to date in terms of complications, bleeding, or efficiency between RL and classic laparoscopy (CL), apart from the duration of surgery, which tends to be longer in RL [ 13 ].…”
Section: Introductionmentioning
confidence: 99%